Territorialidade e identidade no pentecostalismo brasileiro: as marchas para Jesus - Freitas, Esion Fernando de (2015)
This work analyzes the religious field Pentecostal focusing on the Brazilian society. The March for Jesus is our object of analyze, understand as a identitary territory appeared in a context of (reverse)territoriatization of the pentecostal movement. Thus, in this logic (reverse)territorialization we detach the place of the MPJ as that territory (reverse)elaboretes the identity pentecostal immersed in a process of liturgical modifications, mannerin and theological that if it accented in last the thirty years, thus directing the religious identity for the future, not limiting only in detaching traditional elements already of the pentecostal movement, but articulating them with more recent aspects. In this way, beyond (reverse)elaboretes, also we demonstrate Mach as (reverse)assert these identities, and this by means of the visibility that if gets to the being an event carried through in public space and of matrix interdenominational. Thus, larding elements among others the centrality in the persons of Jesus, the Theology of the Battle Spiritual and the Gospel Culture, the March was defined as a flexible territory and shared, contributing for the stabilization of the identitary routes in the sinus of the Brazilian Pentecostalism